Vaccine-Mediated Immunity Against Dengue and the Potential for Long-Term Protection Against Disease - Slifka, Mark K. (Frontiers in Immunology, 2014)
It is estimated that over 2.5 billion people are at risk for contracting dengue, a virus responsible for 50–390 million infections in addition to thousands of hospitalizations and deaths each year. There are no licensed vaccines available to combat this pathogen but substantial efforts are underway to develop live-attenuated, inactivated, and subunit vaccines that will protect against each of the four serotypes of dengue. Unfortunately, the results of a recent Phase IIb efficacy trial involving a tetravalent live-attenuated chimeric dengue virus vaccine have raised questions with regard to our current understanding of vaccine-mediated immunity to this important flavivirus. Here, we will briefly summarize these vaccination efforts and discuss the importance of informative in vivo models for determining vaccine efficacy and the need to establish a quantitative correlate of immunity in order to predict the duration of vaccine-induced antiviral protection.